IMPACT OF PULMONARY HYPERTENSION ON SURGICAL OUTCOMES IN PATIENTS WITH RHEUMATIC MITRAL VALVE DISEASE: A DESCRIPTIVE CROSS SECTIONAL STUDY - Pervaiz, Farrah; Chaudhry, Imtiaz Ahmed; Bakshs, Muhammad; Iqbal, Afsheen; Paracha, Vaqar Ilahi (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To evaluate the early & late outcomes after mitral valve replacement in patients with rheumatic mitral valve disease and moderate to severe pulmonary arterial hypertension. Study Design: Descriptive cross sectional study. Place and Duration of Study: AFIC&NIHD Rawalpindi. Patients and Methods: We analyzed data of 137 patients with mitral valve replacement during 2013.The study included patients with baseline systolic pulmonary artery pressure (sPAP) more than 40 mmHg who underwent elective MVR for rheumatic mitral valve disease. The preoperative, per operative and postoperative clinical characteristics were recorded to assess the short term outcomes (30 days). Preoperative and postoperative transthoracic echocardiography was performed. Patients were followed up for 1 year to assess the late outcomes. Results: In this study forty five patients 17(37.8%) males and 28(62.2%) females with a mean age of 34 years (SD ± 10.3) were included with moderate to severe pulmonary hypertension. The total operative mortality was 5(11.1%). Postoperatively, there was a significant reduction in pulmonary artery systolic pressure in these patients. Conclusion: Mitral valve replacement is safe and effective in patients with moderate to severe pulmonary hypertension and results in significant improvement of pulmonary hypertension, despite relatively higher mortality.